Effects of fleas on nest success of Arctic barnacle geese: experimentally testing the mechanism. (8th May 2019) - de Jong, Margje E.; Wetherbee, Ross; Loonen, Maarten J. J. E.
Abstract : Parasites have detrimental effects on their hosts' fitness. Therefore, behavioural adaptations have evolved to avoid parasites or, when an individual is already in contact with a parasite, prevent or minimize infections. Such anti‐parasite behaviours can be very effective, but can also be costly for the host. Specifically, ectoparasites can elicit strong host anti‐parasite behaviours and interactions between fleas (Siphonaptera) and their hosts are one of the best studied. In altricial bird species, nest fleas can negatively affect both parent and offspring fitness components. However, knowledge on the effects of fleas on precocial bird species is scarce. Research on geese in the Canadian Arctic indicated that fleas have a negative impact on reproductive success. One possible hypothesis is that fleas may affect female incubation behaviour. Breeding females with many fleas in their nest may increase the frequency and/or duration of incubation breaks and could even totally desert their nest. The aim of our study was to 1) determine if a similar negative relationship existed between flea abundance and reproductive success in our study colony of Arctic breeding barnacle geese Branta leucopsis and 2) experimentally quantify if such effects could be explained by a negative effect of nest fleas on female behaviour. We compared host anti‐parasite and incubation behaviour between experimentally flea‐reduced and control nests using wildlife cameras and temperature loggers. We found that flea abundance was negatively associated with hatching success. We found little experimental support, however, for changes in behaviour of the breeding female as a possible mechanism to explain this effect.